Coping with the heterogeneity of external knowledge sources: Corresponding openness strategies and innovation performance - Hamdy Abdelaty; Daniel Weiss (Journal of Innovation & Knowledge, 2023)
Previous studies on open innovation and strategic management have emphasized the positive impact of external knowledge on firms' innovation performance. However, given that external knowledge is widely distributed across a myriad of heterogeneous sources, it presents challenges for both the openness strategy and knowledge accessibility. When designing a firm's openness strategy, the heterogeneity of these external sources must be considered, choosing a form of openness that aligns with the attributes of the targeted sources. The question remains, which form of openness aligns best with which knowledge source and leads to improved innovation performance? Our regression analysis, based on a sample of 3294 German firms from the Mannheim Innovation Panel (MIP) in 2013 and 2017, reveals that utilizing a search strategy toward market sources of knowledge influences innovation performance more positively than a collaboration strategy. Conversely, only collaboration with science-based sources of knowledge has a significant positive impact on innovation performance. We further delve into the implications of these observed results and describe the practical implications for innovation managers.